2013
DOI: 10.1016/j.jpainsymman.2011.12.287
|View full text |Cite
|
Sign up to set email alerts
|

Advance Directives in Japanese Nursing Homes

Abstract: More than half of Japanese nursing homes have introduced advance directives, and additional funding for end-of-life care is related to their introduction. Most nursing homes have adopted instructional directives, especially those providing an explanation and informed consent regarding end-of-life care at the nursing home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…In other literature, the EOL care bonus by the Japanese government had been just introduced (17,18); however, there have been no studies concerning how the EOL care bonus has affected the promotion of EOL care in nursing homes. If it is revealed that the bonus by the Japanese government promotes EOL care in nursing homes, it may contribute to effective EOL care in nursing homes in other developed countries with a rapidly aging population.…”
mentioning
confidence: 99%
“…In other literature, the EOL care bonus by the Japanese government had been just introduced (17,18); however, there have been no studies concerning how the EOL care bonus has affected the promotion of EOL care in nursing homes. If it is revealed that the bonus by the Japanese government promotes EOL care in nursing homes, it may contribute to effective EOL care in nursing homes in other developed countries with a rapidly aging population.…”
mentioning
confidence: 99%
“…Before any comprehensive DNR policy is developed, advance directives (Takezako et al . ) or physician orders for life‐sustaining treatment (POLST) forms (Meyers et al . ) should also be considered in NH populations and in end‐of‐life cases (Silveira et al .…”
Section: Discussionmentioning
confidence: 99%
“…ADs are now in the stage of introduction, as reflected in the guidelines from the 'Special Committee in National Bioethics Committee' in Korea (15). Although 58.4% of nursing homes in Japan adopted ADs, only 39.9% offered the AD form with which a patient can specifically select their choice of treatment (16). In mainland China, palliative care is developing slowly, and there is currently no case law regarding AD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have assumed that Japanese people were concerned with the potential risk of excessive withdrawal of treatment following the acceptance of ADs, considering the context of national health insurance (NHI), which covers most medical expenses (16,21). This potential problem of excessive pressure to withdraw treatment is also the case in Korea, where national healthcare insurance covers at least part of the medical expenses of every citizen and death-related expenses constitute 8.3% of the total NHI expenditure (22).…”
Section: Discussionmentioning
confidence: 99%